Клінічні та прогностичні чинники перебігу інфаркту міокарда у хворих, яким проведена тромболітична терапія - Матузок, О. Е.; Матузок, О. Э.; Matuzok, O. E. (Запорізький державний медичний університет, 2018)
Дисертація присвячена удосконаленню реперфузійної стратегії лікування гострого коронарного синдрому (ГКС) та прогнозуванню перебігу інфаркту міокарда (ІМ) у хворих, яким проведена тромболітична терапія (ТЛТ), на підставі вивчення взаємозв’язків клініко-інструментальних, генетичних та біохімічних чинників. У роботі отримані нові наукові дані щодо факторів, які асоційовані з ефективністю ТЛТ та впливають на глибину ураження міокарда, післяінфарктну дилатацію ЛШ, госпітальний і віддалений прогноз хворих на ГКС з елевацією сегменту ST. Встановлені прогностичні рівні лабораторних показників, асоційованих з неефективною ТЛТ. Поглиблені дані щодо зв’язку між порушенням ендотеліальної функції та вираженістю системного запалення, між алельним станом Т-786С поліморфізму гену eNOS в та факторами ризику кардіоваскулярних ускладнень у хворих на ГКС з елевацією сегменту ST. Диссертация посвящена усовершенствованию реперфузионной стратегии лечения острого коронарного синдрома (ОКС) и прогнозированию течения инфаркта миокарда (ИМ) у больных, которым проведена тромболитическая терапия (ТЛТ), на основании изучения взаимосвязей клиникоинструментальных, генетических и биохимических факторов. В работе получены новые научные данные относительно факторов, ассоциированных с эффективностью ТЛТ и влияющих на глубину поражения миокарда, постинфарктную дилатацию ЛЖ, госпитальный и отдаленный прогноз больных ОКС с элевацией сегмента ST. Установлены прогностические уровни лабораторных показателей, ассоциированных с неэффективностью ТЛТ. Углублены данные относительно связи между нарушением эндотелиальной функции и выраженностью системного воспаления, между аллельным состоянием Т-786С полиморфизма гена eNOS и факторами риска сердечнососудистых осложнений у больных ОКС с элевацией сегмента ST. The aim of the dissertation was improvement of the reperfusion strategy of treatment of acute coronary syndrome and prognosis of myocardial infarction course in patients treated with thrombolytic therapy, on the basis of study of relationships of clinical, instrumental, genetic and biochemical factors. Study results were based on prospective and retrospective examination of 207 patients with acute coronary syndrome with ST segment elevation after intravenous fibrinolysis. In retrospective group (data from 100 archive medical cards of hospitalized patients) frequency of pre-hospital fibrinolysis was 11%. Medicamental treatment had multiple deviations from the guidelines. Prospective group consisted of 107 patients. All patients were given medicamental treatment in compliance with the guidelines. Frequency of pre-hospital fibrinolysis was 37%. Blood sampling for highsensitive C-reactive protein (hsCRP) and asymmetric dimethylarginine (ADMA), leucocyte count was performed at admission. ADMA level was assessed with highperformance liquid chromatography. 7 patients died, in-hospital mortality was 6,5%. In (12±2) months after study entry we collected the information regarding the complications and in 60 patients cardiac ultrasound was repeated. Medicamental treatment in compliance to the guidelines helped to improve the course of the disease. Risk of the endpoint (acute left ventricular (LV) aneurism + inhospital mortality) decreased from 25% in the retrospective to 11,2% in prospective group (p=0,02), odds ratio = 2,64 [1,23-5,67]. Patients who carried C allele of T-786C polymorphism of eNOS endothelial nitric oxide synthase (eNOS) gene were significantly more likely to have a history of arterial hypertension and type 2 diabetes mellitus (T2DM). In regression analysis, presence of C allele was an independent factor of LV volumes increase in myocardial infarction (MI) acute phase. ADMA increase was associated with increase of hsCRP, younger age, higher end diastolic volume (EDV) and admission glycemia increase, decrease of glomerular filtration rate and lower body mass index, longer time to fibrinolysis (regression analysis). We demonstrated the relationship between ADMA level and smoking, increase of time to fibrinolysis, ultrasonic parameters - increase of EDV and end systolic volume (ESV), decrease of ejection fraction (EF), higher hsCRP and glycemia at admission, higher heart rate on the 2nd day of the MI. HsCRP level correlated significantly with history of T2DM and time to fibrinolysis, and was independently related to increase of end-diastolic and end- systolic diameters during MI acute phase in regression analysis. Patients with higher leucocyte count level at admission were significantly more likely to have anterior MI localization, higher maximum MB-fraction of creatine phosphokinase (MB-CPK) level and admission hsCRP. They had the higher frequency of complications at acute phase of MI and during follow-up and lower EF. We have shown the direct correlation of leucocyte count with the highest MB-CPK level and ultrasonic parameters at follow-up. Fibrinolysis was found to be effective in 56 (56%) patients, not effective in 44 (44%). Patients with non-effective fibrinolysis had higher TIMI risk score and heart rate on the 2nd day of the disease, higher maximum MB-CPK, higher EDV and ESV and lower EF. Insufficient fibrinolysis efficacy was associated with laboratory parameters at admission - leukocyte count >11x109/l, ADMA >1,4 mkmol/l, hsCRP >11,03 mg/l (Receiver Operating Characteristic analysis). Patients who did not develop pathologic Q wave had shorter time to fibrinolysis, lower hsCRP, were more likely to receive pre-hospital fibrinolysis. We found an increased risk of complications during (12±2) months follow-up in patients with history of angina, anterior MI localization, lower EF at study entry, hsCRP increase, longer smoking duration, and in females (regression analysis). In regression model, risk of postinfarction LV dilatation increased with smaller left atrium size and lower LV mass at study entry, in current smokers, in case of hsCRP increase, history of angina, and in anterior MI. Patients with higher hsCRP and ADMA, lower EDV, ESV, LV myocardium mass had higher risk of postinfarction LV dilatation.
Клинические и прогностические факторы течения инфаркта миокарда у больных, которым проведена тромболитическая терапия
Clinical and prognostic factors of myocardial infarction course in patients treated with thrombolytic therapy
Keywords: інфаркт міокарда; тромболітична терапія; С-реактивний білок; лейкоцитоз; Т-786С поліморфізм гену eNOS; асиметричний діметиларгінін; дилатація ЛШ; прогноз; инфаркт миокарда; тромболитическая терапия; С-реактивный белок; Т-786С полиморфизм гена eNOS; асимметричный диметиларгинин; дилатация ЛЖ; myocardial infarction; thrombolytic therapy; C-reactive protein; leukocytosis; T-786C polymorphism of eNOS gene; asymmetric dimethylarginine; LV dilatation; prognosis